中国湖泊科学进展 - 杨桂山 姜加虎 王苏民 (Journal of geographical sciences, 2004)
［1］Dou Hongshen, Jiang Jiahu, 2000. Dongting Lake. Hefei: Chinese Science and Technology University Press. (in Chinese) ［2］Gao Licun, 1998. Comprehensive Techniques of Breeding Aquatics by Purse Net. Nanjing: Jiangsu Science and Technology Press. (in Chinese) ［3］Huang Yiping, 2001.Water Environment and Pollution Control of Taihu Lake. Beijing: Science Press. (in Chinese) ［4］Jin Xiangcan, Tu Qingying, 1990. Chinese Lake Eutrophication. Beijing: China′s Environment Science Press. (in Chinese) ［5］Jin Xiangcan, Tu Qingying, 1995.Chinese Lake Environment (vol. 1). Beijing: China Ocean Press. (in Chinese) ［6］Nanjing Institute of Geography and Limnology, CAS, 1989. Environment and Sediment of Duanxian Lake in Yunnan Province. (in Chinese) ［7］Nanjing Institute of Geography and Limnology, CAS, 1993. Taihu Lake. Beijing: China Ocean Press. (in Chinese) ［8］Nanjing Institute of Geography and Limnology, CAS, 1999. Fuxian Lake. Beijing: China Ocean Press. (in Chinese) ［9］Qin Boqiang, Hu Weiping, Chen Weimin et al., 2004. Process and Mechanism of Water Environment Evolution of Taihu Lake. Beijing: Science Press. (in Chinese) ［10］Shi Chengxi, 1989.Overview of Chinese Lakes. Beijing: Science Press. (in Chinese) ［11］Tu Qingying, Gu Dingxi, Yin Chengqing et al., 1990. Chaohu Lake. Hefei: Chinese Science and Technology University Press. (in Chinese) ［12］Wang Hongdao, 1978. Water Resources of Chinese Lakes. Beijing: Agriculture Press. (in Chinese) ［13］Wang Sumin, Dou Hongshen, 1998. A Directory of Lakes in China. Beijing: Science Press. (in Chinese) ［14］Yang Guishan, Wang Dejian, Chen Wen et al., 2003. Economic Development, Water Environment and Water Disaster in Taihu Lake Watershed. Beijing: Science Press. (in Chinese) ［15］Yu Ge, Xue Bin, Liu Jian et al., 2001. Chinese Lakes Evolution and Palaeoclimate Dynamics. Beijing:Meteorological Press. (in Chinese) ［16］Zhu Haihong, Zhang Ben, 1997. Boyang Lake. Hefei: Chinese Science and Technology University Press. (in Chinese) ［17］Zhu Songquan, Dou Hongshen, 1993. Hongze Lake. Hefei: Chinese Science and Technology University Press. (in Chinese)